ANALYSIS OF GRADE VIII STUDENTS’ ERRORS IN SOLVING TWO-VARIABLE LINEAR EQUATION SYSTEMS BASED ON NEWMAN’S PROCEDURE - Anggraini, Yurika Fajri; Anggraini, Anggraini; Sugita, Gandung; Sukayasa, Sukayasa (JME (Journal of Mathematics Education), 2026)
This study aims to describe the errors made by Grade VIII H students at SMP Negeri 2 Palu in solving word problems on systems of linear equations in two variables based on Newman’s procedure. This study employed a descriptive qualitative design. The subjects consisted of three students selected purposively based on the frequency and variation of errors identified through written tests and teacher recommendations. Data were collected through written tests and interviews, while data credibility was ensured through member checking. The results showed that students experienced four dominant types of errors, namely comprehension, transformation, process skill, and encoding errors. These errors were mainly caused by students’ difficulties in understanding problem information, constructing mathematical models, carrying out procedural calculations, and formulating final answers appropriately. The findings of this study provide important implications for mathematics learning, particularly in strengthening students’ conceptual understanding, mathematical modeling skills, and systematic problem-solving abilities.